2011
DOI: 10.1108/13612021111169951
|View full text |Cite
|
Sign up to set email alerts
|

Challenging market conventions

Abstract: PurposeIn the UK, while fashion apparel purchasing is available to the majority of consumers, the main supermarkets seem – rather against the odds and market conventions – to have created a new, socially‐acceptable and legitimate, apparel market offer for young children. This study aims to explore parental purchasing decisions on apparel for young children (below ten years old) focusing on supermarket diversification into apparel and consumer resistance against other traditional brands.Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Holmlund et al [25] showed that for mature women, fashion style is one of the significant factors they consider when purchasing clothes. De Kervenoael et al [26] provided evidence that besides functional apparel values (i.e., cost, quality, guarantee, warranty, etc. ), intuitive factors such as fashion style are highly important when buying fashion apparel.…”
Section: Impact Of Fashion Style Preference On Apparel Production And...mentioning
confidence: 99%
“…Holmlund et al [25] showed that for mature women, fashion style is one of the significant factors they consider when purchasing clothes. De Kervenoael et al [26] provided evidence that besides functional apparel values (i.e., cost, quality, guarantee, warranty, etc. ), intuitive factors such as fashion style are highly important when buying fashion apparel.…”
Section: Impact Of Fashion Style Preference On Apparel Production And...mentioning
confidence: 99%
“…Parentsʼ decisions while purchasing children's clothing are influenced by sizing, price, quality, ease of shopping, and payment options (Haluk Köksal, 2007, p. 79). Price tops quality for families with young children due to the constant need for updating the wardrobe with the correct clothing size (De Kervenoael, Canning, Palmer, & Hallsworth, 2011;Haluk Köksal, 2007).…”
Section: Clothing Selectionmentioning
confidence: 99%
“…Dressing an infant child is a task that involves planning, division of responsibilities, and selecting appropriate clothes for different occasions. Previous research about children and fashion focused on historical depictions of childhood (Higonnet & Albinson, 1997;Paoletti, 2012); evaluation of child-parent relationships under subjects related to identity (Cohen, 2013;Doucet, 2009;De Mol & Buysse, 2008;König, 2008;Rawlins, 2006), consumerism and consumption (Afflerback, 2014;Andersen et al, 2007;De Kervenoael et al, 2011;Heath et al, 2016;Horan et al, 2007;Koksal, 2007;Martens et al, 2004;McNeill & Graham, 2014;Petersen & Riisberg, 2017;Ritch & Schroder, 2012). Research inquiry often focuses on the motherdaughter (or mother-infant child) dyad, overlooking the father's role.…”
Section: Chapter Six: Conclusionmentioning
confidence: 99%